1998
DOI: 10.1046/j.1523-1755.1998.00131.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered anionic GBM components in monoclonal antibody against slit diaphragm-injected proteinuric rats

Abstract: These results show that the injection of mAb 5-1-6 induced a perturbation of the charge- and probably the size-selective glomerular filtration barrier. The observed reduction in the levels of various negatively charged substances resulted in massive proteinuria, implying that alteration of target antigens can affect the integrity of the GBM constituents maintaining the normal barrier function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…When glomerular permeability for albumin is enhanced, the distribution of albumin in the GBM would be expected to shift towards the outer (epithelial) side of the GBM. This expected alteration in the distribution of endogenous albumin could in fact be demonstrated in a previous study in proteinuric rats [14]. Therefore, we believe that it is possible to detect and interpret subtle changes of permeability in the glomerular filter by studying alterations in the localization of endogenous albumin using the present technique.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…When glomerular permeability for albumin is enhanced, the distribution of albumin in the GBM would be expected to shift towards the outer (epithelial) side of the GBM. This expected alteration in the distribution of endogenous albumin could in fact be demonstrated in a previous study in proteinuric rats [14]. Therefore, we believe that it is possible to detect and interpret subtle changes of permeability in the glomerular filter by studying alterations in the localization of endogenous albumin using the present technique.…”
Section: Discussionsupporting
confidence: 75%
“…An epitope on an antigen of the slit diaphragm, which is recognized by MoAb 5-1-6, has been shown to regulate glomerular permeability in rats [13,14,26] and al- terations in the quantity and/or distribution of this antigen could be expected to be associated with proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…The GBM poses anionic sites (33) consisted of glucosaminoglycans (34) and the decrement of such sites is presumed to reflect dysfunction of the charge selective barrier in nephrotic syndrome (26,34,35). In addition, the differential clearance study by Lund et al (36) using neutral and native forms of albumin indicated that the fractional clearance of neutral albumin …”
Section: Takahashi Et Almentioning
confidence: 99%
“…Recent studies by Jeansson and Haraldsson (41) suggested the importance of endothelial glycocalyx in the charge-selective property of GCW. Unless impairment of the slit diaphragm may influence the anionic sites of GBM (35), the group A diseases are not likely to completely lose their charge-selective properties. This is supported by the cases of FCNS and FSGS since these diseases showed a worse SI with a better CSI than group A.…”
Section: Charge Barrier In Glomerular Diseasesmentioning
confidence: 99%
“…We have already reported some investigations of the pathogenesis of mAb 5-1-6 nephropathy, 6,40,[58][59][60][61][62][63] and investigations of the expression of mAb 5-1-6 antigen in the proteinuric state [64][65][66][67] and in the developing glomeruli. 48,68 All our observations on the expression of mAb 5-1-6 antigen reported previously should be interpreted as observations on the expression of nephrin.…”
Section: Anti-nephrin Mab 5-1-6 Nephropathymentioning
confidence: 99%